Measuring the power of parties within US Government from 1993 to 2018: New key variables - Matteo Laruffa (European Journal of American Studies)
The article describes a new theoretical framework and empirical method to understand the power of parties within the U.S. Government. Political parties are not simply critical means by which citizens participate in their government, but also foundational to a pluralist political society and play an active role in defending the constitutional principles of liberal institutions and democracy. The first part of the article provides an overall glance of the dimensions used for observing the political power during democratic crises. Then, it is concerned with the identification of some “compelling” dimensions of political behavior of parties, and an empirical analysis of the changes occurred in the American institutions conducted in a long-term perspective of the last 25 years. Indeed, the second part accurately refers to the degree of which its political balances, institutional guarantees and constitutional design provide effective defense to democracy. Finally, these results invite us to watch at the current troubles with a moderate share of realism on the future capacity of democracy in the U.S. to survive.